Anthropometric Indices As Predictors To Blood Gases Changes Among Infantry Military Personnel - Ainsah Omar; Mohd Rawi Mohd Norddin; Osman Che Bakar; Ahmad Hakim Osman; Arina Amalina Osman; Maslinda Mohd Kasim; Ahmad Zakuan Kamarudin; Zul Azlin Razali (International Journal of Health Sciences and Research, 2024)
Non-Indexed Publication